Inter‐Metal Interaction with a Threshold Effect in NiCu Dual‐Atom Catalysts for CO2 Electroreduction - Yao, Dazhi; Tang, Cheng; Zhi, Xing; Johannessen, Bernt; Slattery, Ashley; Chern, Shane; Qiao, Shi‐Zhang (Advanced materials (Weinheim), 2023)
Dual‐atom catalysts (DACs) have become an emerging platform to provide more flexible active sites for electrocatalytic reactions with multi‐electron/proton transfer, such as the CO2 reduction reaction (CRR). However, the introduction of asymmetric dual‐atom sites causes complexity in structure, leaving an incomprehensive understanding of the inter‐metal interaction and catalytic mechanism. Taking NiCu DACs as an example, herein, a more rational structural model is proposed, and the distance‐dependent inter‐metal interaction is investigated by combining theoretical simulations and experiments, including density functional theory computation, aberration‐corrected transmission electron microscopy, synchrotron‐based X‐ray absorption fine structure, and Monte Carlo experiments. A distance threshold around 5.3 Å between adjacent NiN4 and CuN4 moieties is revealed to trigger effective electronic regulation and boost CRR performance on both selectivity and activity. A universal macro‐descriptor rigorously correlating the inter‐metal distance and intrinsic material features (e.g., metal loading and thickness) is established to guide the rational design and synthesis of advanced DACs. This study highlights the significance of identifying the inter‐metal interaction in DACs, and helps bridge the gap between theoretical study and experimental synthesis of atomically dispersed catalysts with highly correlated active sites. Investigating the inter‐metal site distance effect of dual‐atom catalysts (DACs) can not only promote the full potential of DACs, but also guide the design of advanced atomically dispersed catalysts. In this work a peripherally distributed NiCu DAC is employed as a case study to investigate the distance (d)‐dependent inter‐metal interaction, and a newly proposed macro‐descriptor is provided as the guidance for future designing DACs.